Elegy - Oliver, Valerie Cassel (Aperture, 2023)
"Dawoud Bey focuses on the landscape to create a portrait of the early African American presence in the United States. Renowned for his Harlem street scenes and expressive portraits, Dawoud Bey continues his ongoing series on African American history. Elegy brings together Bey's three landscape series to date--Night Coming Tenderly, Black (2017); In This Here Place (2021); and Stoney the Road (2023)--elucidating the deep historical memory still embedded in the geography of the United States. Bey takes viewers to the historic Richmond Slave Trail in Virginia, where Africa ns were marched onto auction blocks; to the plantations of Louisiana, where they labored; and along the last stages of the Underground Railroad in Ohio, where fugitives sought self-emancipation. Essays by the exhibition's curator, Valerie Cassel Oliver, and scholars LeRonn P. Brooks, Imani Perry, and Christina Sharpe illuminate the work. By interweaving these bodies of work into an elegy in three movements, Bey doesn't merely evoke history, he retells it through historically grounded images that challenge viewers to go beyond seeing and imagine lived experiences."--Publisher's website
Impressum: Produced by and copublished with the Virginia Museum of Fine Arts on the occasion of the exhibition, "Dawoud Bey: Elegy", curated by Valerie Cassel Oliver and first presented at the Virginia Museum of Fine Arts, November 18, 2023 - February 25, 2024
Keywords: Bey, Dawoud -- 1953-; Schwarzweißfotografie; Bey, Dawoud / 1953- / Exhibitions; Bey, Dawoud / 1953- / Interviews; Slave trade / United States; Landscape photography / United States / 21st century / Exhibitions; Black-and-white photography / 21st century; Photography, Artistic / 21st century; Landscape photography; Black-and-white photography; Photography, Artistic; United States; Exhibition catalogs; Ausstellungskatalog -- Virginia Museum of Fine Arts -- 18.11.2023-25.02.2024 -- Richmond, Va.; Bildband